'No longer bulletproof' : Aotearoa/New Zealand men discuss aging and masculinity : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology, Massey University, Wellington, New Zealand - Lindsay, Samuel (Massey University, 2020)
Research on men has proliferated within in recent decades. However, much of this research has focused on younger masculinities. While research on older men has also increased in recent years, there remains a lack of research on the ways in which masculinities are impacted by aging – particularly within a A/NZ context. This study took a social constructionist approach to exploring the ways in which A/NZ men make sense of masculinity as they age. Twenty-six men between the ages of 65 and 90 were interviewed and interviews were recorded, transcribed, and analysed using a thematic analysis approach. Analysis revealed a range of themes related to the operations of gendered power such as the invisibility of masculinity, egalitarianism, and a backlash against feminists. The men also reiterated dominant themes related to active aging, enjoyment, disengagement and decline, provision, masculinity as limiting, and increases in wisdom and insight. The ways in which themes of masculinity intersected with those related to aging were discussed with participants. The themes were related to theories of gender as performance, hegemonic masculinity, masculine capital, and selective optimisation and compensation. Implications, limitations, and suggested future directions are also discussed.
Keywords: Older men; New Zealand; Social conditions; Psychology; Attitudes; Aging; Social aspects; Masculinity; 520106 Psychology of ageing; 520502 Gender psychology